1995
DOI: 10.1073/pnas.92.21.9580
|View full text |Cite
|
Sign up to set email alerts
|

The 94- to 97-kDa mouse macrophage membrane protein that recognizes oxidized low density lipoprotein and phosphatidylserine-rich liposomes is identical to macrosialin, the mouse homologue of human CD68.

Abstract: The 94-to 97-kDa mouse macrophage membrane protein that recognizes oxidized low density lipoprotein and phosphatidylserine-rich liposomes is identical to macrosialin, the mouse homologue of human CD68

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
186
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(190 citation statements)
references
References 41 publications
3
186
0
1
Order By: Relevance
“…Our conclusion that the Kupffer cell oxLDL receptor and macrosialin are identical implies that the oxLDL receptor on mouse peritoneal macrophages, which was described by Steinberg and co-workers [11,14], is the same receptor as the Kupffer cell oxLDL receptor described in this paper. The difference in molecular mass (94-97 kDa and 115-120 kDa respectively) between the two could then be explained by differences in glycosylation, since Rabinowitz and Gordon [17,18] showed that glycosylation of macrosialin can differ between different macrophage populations, and is dependent on the state of cell stimulation.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Our conclusion that the Kupffer cell oxLDL receptor and macrosialin are identical implies that the oxLDL receptor on mouse peritoneal macrophages, which was described by Steinberg and co-workers [11,14], is the same receptor as the Kupffer cell oxLDL receptor described in this paper. The difference in molecular mass (94-97 kDa and 115-120 kDa respectively) between the two could then be explained by differences in glycosylation, since Rabinowitz and Gordon [17,18] showed that glycosylation of macrosialin can differ between different macrophage populations, and is dependent on the state of cell stimulation.…”
Section: Resultssupporting
confidence: 84%
“…Recently, Ramprasad et al [14] found evidence that the 94-97 kDa oxLDL receptor present on mouse peritoneal macrophages is identical with macrosialin. Macrosialin is the mouse homologue of human CD68, a heavily glycosylated protein present on macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TSP, or a 140-kDa COOH-terminal domain proteolytic fragment from this protein [13], forms a bridge between the M receptor complex and the PMN ligand specific for TSP. Finally, the lipid receptor responsible for PMN recognition, although not formally characterized, is specific for phosphatidylserine [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many receptors could be involved in BSDL uptake and transcytosis throughout Int407 cells (Ramprasad et al, 1995;Adachi et al, 1997;Dhaliwal and Steinbrecher, 1999;Shirai et al, 1999;Cai et al, 2001;Lobo et al, 2001;Werder et al, 2001;Gillotte-Taylor et al, 2001). Among them the lectin-like oxidized LDL receptor or LOX-1, a 50-kDa protein detected in nearly all tissues examined (Sawamura et al, 1997) has retained our attention.…”
Section: Lox-1 Implication In Bsdl Transcytosismentioning
confidence: 99%